Cultural adaptation of a children's weight management programme: Child weigHt mANaGement for Ethnically diverse communities (CHANGE) study - Miranda Pallan; Tania Griffin; Kiya Hurley; Emma Lancashire; Jacqueline Blissett; Emma Frew; Paramjit Gill; Laura Griffith; Kate Jolly; Eleanor McGee; Jayne Parry; Janice L. Thompson; et al. (BMC, 2019)
Abstract Background Childhood obesity prevalence continues to be at high levels in the United Kingdom (UK). South Asian children (mainly Pakistani and Bangladeshi origin) with excess adiposity are at particular risk from the cardiovascular consequences of obesity. Many community-based children's weight management programmes have been delivered in the UK, but none have been adapted for diverse cultural communities. The aim of the Child weigHt mANaGement for Ethnically diverse communities (CHANGE) study, was to culturally adapt an existing children's weight management programme for children aged 4-11 years so that the programme was more able to meet the needs of families from South Asian communities. Methods The adaptation process was applied to First Steps, an evidence informed programme being delivered in Birmingham (a large, ethnically diverse city). A qualitative study was undertaken to obtain the views of South Asian parents of children with excess weight, who had fully or partially attended, or who had initially agreed but then declined to attend the First Steps programme. The resulting data were integrated with current research evidence and local programme information as part of a cultural adaptation process that was guided by two theoretical frameworks. Results Interviews or focus groups with 31 parents in their preferred languages were undertaken. Themes arising from the data included the need for convenient timing of a programme in a close familiar location, support for those who do not speak English, the need to focus on health rather than weight, nutritional content that focuses on traditional and Western diets, more physical activity content, and support with parenting skills. The data were mapped to the Behaviour Change Wheel framework and Typology of Cultural Adaptation to develop an intervention programme outline. The research evidence and local programme information was then used in the detailed planning of the programme sessions. Conclusions The process of cultural adaptation of an existing children's weight management programme resulted in a theoretically underpinned programme that is culturally adapted at both the surface and deep structural levels. Trial registration ISRCTN81798055, registered: 13/05/2014.